Single-Mode Tapered Vertical SU-8 Waveguide Fabricated by E-Beam Lithography for Analyte Sensing - Yu Xin; Gregory Pandraud; Yongmeng Zhang; Paddy French (Sensors, 2019)
In this paper, we propose a novel vertical SU-8 waveguide for evanescent analyte sensing. The waveguide is designed to possess a vertical and narrow structure to generate evanescent waves on both sides of the waveguide’s surface, aimed at increasing the sensitivity by enlarging the sensing areas. We performed simulations to monitor the influence of different parameters on the waveguide’s performance, including its height and width. E-beam lithography was used to fabricate the structure, as this one-step direct writing process enables easy, fast, and high-resolution fabrication. Furthermore, it reduces the sidewall roughness and decreases the induced scattering loss, which is a major source of waveguide loss. Couplers were added to improve the coupling efficiency and alignment tolerance, and will contribute to the feasibility of a plug-and-play optical system. Optical measurements show that the transmission loss is 1.03 ± 0.19 dB/cm. The absorption sensitivity was measured to be 4.8 dB per refractive index unit (dB/RIU) for saline solutions with various concentrations.